Úloha pôvodnej a modernej architektúry pri estetizácii verejného priestoru - Jana Pecníková, Anna Slatinská (2018)
The contribution deals with the topic of aesthetization of public space and use of modern architecture in historically valuable environment. These issues have been debated for a long time. The aim of our contribution is conneced with questions concerning the topic of aesthetization. We defined the following questions: How can coexistence of history and present state of architectonic works reflect the city's image. Can symbiosis of historical and contemporary, old and new create more suitable conditions for realizations of cultural activities? Can architecture of today be regarded in terms of respecing the archictonic language of the past and does it respect past monuments with honor? Public spaces that should play its representative function are to a great extent influenced by interventions into historical architectural structure. In the conclusion of our contribution we present the reader with several famous examples from Slovakia as well as from abroad which confirm that aesthetisation of public space is to a great extent dependent on adherence to and respect of cultural traditions.